Sistem Kekeluargaan Dalam Islam: (Interpretasi Qs. An Nisa 22-23) - Rusik Rusik (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Marriage is a contract that contains the prohibition of something that was strictly forbidden before. This is a relationship between the opposite sex. Thus, sufficient understanding is needed regarding the conditions and pillars that must be fulfilled so that the marriage is carried out in accordance with religious provisions. In Indonesia, the family system—the implementation of which determines whether or not to marry—varies. From here the author is interested in studying mahram relationships that have been determined by religion. The aim of this research is to describe and classify who can marry and who cannot, based on the interpretation of the holy Koran. This research is library research, which is descriptive qualitative in nature by conducting a literature review related to the themes presented. The data is then analyzed and produces conclusions. The results of the research show that the family relationships implemented are in accordance with the provisions provided by the Shari'a. It is not permissible to marry only if it is customary and does not touch halal and haram within a religious framework, so that existing marriages are valid because they fulfill the requirements and are in harmony with each other religiously.